Sosialisasi Pencegahan Golput kepada Kelompok Lansia pada Pemilu 2024 di Desa Dangin Puri Kauh, Kota Denpasar - Asti Mulyawati, Ni Kadek Ayu; Haes, Putri Ekaresty (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
This community service activity aims to provide information about election socialisation to the Elderly group. Community service activities are carried out in Dangin Puri Kauh Village, Denpasar City by conducting preliminary observations and interviews so that the conditions of the village can create a work programme. Based on the results of the analysis, the elderly group was chosen to receive socialisation about the 2024 elections.